Forms of Life and Cultural Endowments. - Peterson II, Victor (Pluralist)
Thus, given coordinates I n i , to formalize a point at which that individual is that individual with the least assumptions is to formalize when I f i ( I n i ) = I n i , making I n i = 0. It follows that successive expressions from that individual, instantiating its being a member of a particular domain, are represented I f i ( I n i + 1), for I n i = I n i , so I f i ( I n i ) = I n i -successor. Given these conditions, it follows that if I n i = 0 is a member of some form of life and for all I n i , if I n i is a member, then so are I n i -successors, then all I n i -expressions are members of that form of life. If those points do not line up with the grid (= reference frame) organizing a state of affairs, points considered as a function of coordinates between the integer scale on each axis allow us to enumerate irrational expressions that are nevertheless real.